Search for rare B0(s) → μ+μ−μ+μ− decays - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
A search for the decays B0s→μ+μ−μ+μ− and B0→μ+μ−μ+μ− is performed using data, corresponding to an integrated luminosity of 1.0 fb−1, collected with the LHCb detector in 2011. The number of candidates observed is consistent with the expected background and, assuming phase-space models of the decays, limits on the branching fractions are set: B(B0s→μ+μ−μ+μ−)<1.6(1.2)×10−8 and B(B0→μ+μ−μ+μ−)<6.6(5.3)×10−9 at 95% (90%) confidence level. In addition, limits are set in the context of a supersymmetric model which allows for the B0(s) meson to decay into a scalar (S) and pseudoscalar particle (P), where S and P have masses of 2.5 GeV/c and 214.3 MeV/c, respectively, both resonances decay into μ+μ−. The branching fraction limits for these decays are B(B0s→SP)<1.6(1.2)×10−8 and B(B0→SP)<6.3(5.1)×10−9 at 95% (90%) confidence level.